2006
DOI: 10.1093/jxb/erl235
|View full text |Cite
|
Sign up to set email alerts
|

Altered cytokinin metabolism affects cytokinin, auxin, and abscisic acid contents in leaves and chloroplasts, and chloroplast ultrastructure in transgenic tobacco

Abstract: Cytokinins (CKs) are involved in the regulation of plant development including plastid differentiation and function. Partial location of CK biosynthetic pathways in plastids suggests the importance of CKs for chloroplast development. The impact of genetically modified CK metabolism on endogenous CK, indole-3-acetic acid, and abscisic acid contents in leaves and isolated intact chloroplasts of Nicotiana tabacum was determined by liquid chromatography/mass spectrometry and two-dimensional high-performance liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 59 publications
3
43
0
1
Order By: Relevance
“…Cytokinins have long been implicated in chlorophyll synthesis [30] although this not always results in an increased concentration in plant tissues [32]. In our experiments, chlorophyll concentration per unit dry weight was unaffected by BAP treatment.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Cytokinins have long been implicated in chlorophyll synthesis [30] although this not always results in an increased concentration in plant tissues [32]. In our experiments, chlorophyll concentration per unit dry weight was unaffected by BAP treatment.…”
Section: Discussionmentioning
confidence: 49%
“…Apriori, both alternatives appeared as likely since there is abundant experimental or bibliographic support: In our previous paper [3] it was shown that BAP increased E. aureum final leaf size and decreased the phyllochron, but cytokinins are also well known to promote the efficiency of the photosynthetic apparatus [30].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that chloroplast biogenesis is controlled by cytokinins (CKs) and exogenously applied CKs can stimulate development of chloroplasts from proplastids, amyloplasts, and etioplasts (after Polanska et al 2007). It has been revealed that this effect was mediated by up-regulation of the expression of some plastid-related genes, both of plastid and nuclear origin.…”
Section: Discussionmentioning
confidence: 99%
“…5). Overexpression of AtCKX3 reduces cytokinin levels in a distant relative of Phtheirospermum, Nicotiana tabacum (27), and caused various cytokinin-deficient phenotypes in Arabidopsis and N. tabacum (11,28). Thus, we reasoned that overexpressing AtCKX3 in Phtheirospermum would also reduce parasite cytokinin levels.…”
Section: Phtheirospermum Elevates Host Cytokinin Levels Independently Ofmentioning
confidence: 99%